Molecular Chromophore-DNA Architectures With Fullerenes: Optical Properties and Solar Cells - Müller, Sara; Manger, Felix; Graf von Reventlow, Lorenz; Colsmann, Alexander; Wagenknecht, Hans-Achim (Frontiers in Chemistry, 2021)
Supramolecular chemistry allows the construction of complex molecular architectures and the design of collective photophysical properties. DNA is an attractive template to build such supramolecular architectures due to its helical structure, the defined distances between the bases and the canonical base pairing that results in precise control of the chromophore position. The tailored properties of DNA-templated supramolecules eventually allow their implementation into optoelectronic applications. For the generation of free charge carriers from photo-generated excitons, fullerenes can be utilized. We synthesized two fullerene derivates, one of which binds by electrostatic interactions to single-stranded DNA, while the other contains two 2’-deoxyuridine moieties and assembles specifically along oligo‐2′‐deoxyadenosines (dA20) as DNA template. The DNA-directed assembly of both fullerenes in aqueous solution was investigated by UV/Vis absorbance and circular dichroism (CD) spectroscopy. The specific interactions with DNA make fullerenes with the 2’-deoxyuridine moieties a significantly better component for supramolecular DNA architectures. We studied the fluorescence quenching of both fullerenes with a DNA chromophore assembly. To investigate one of the key properties for optoelectronic applications, that is is the supramolecular structure of the DNA-based assemblies in the solid phase, we characterized the CD of supramolecular chromophore-DNA architectures in thin films. Remarkably, the helical chirality of the chromophore assemblies that is induced by the DNA template is conserved even in the solid state. Upon implementation into organic solar cells, the external quantum efficiency measurements showed charge carrier generation on all three chromophore components of the DNA assemblies. The fullerenes with the 2’-deoxyuridine moieties enhance the quantum efficiency of the conversion process significantly, demonstrating the potential of DNA as structural element for ordering chromophores into functional -systems, which may be employed in future organic solar cells.